2023
DOI: 10.1111/bjhp.12682
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that implementation intentions reduce self‐harm in the community

Abigail Paterson,
Mark A. Elliott,
Louise A. Brown Nicholls
et al.

Abstract: ObjectivesImplementation intentions are ‘IF‐THEN’ plans that encourage goal‐intended behaviour. This study was designed to test whether an intervention encouraging the formation of implementation intentions can reduce self‐harm in the community.DesignA randomized controlled design was used.MethodsAt pre‐intervention, outcome variables (self‐harm in both specified and unspecified critical situations and suicidality) and potential moderators of implementation intentions (goal intention, mental imagery, and expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
1
1
0
Order By: Relevance
“…In support of hypothesis 1, university students randomized to a VHS condition attended a significantly greater proportion of synchronous online lectures over the 11-week teaching semester than did students randomly assigned to a control condition (59% vs. 48%). These findings are consistent with previous studies of other behaviours, which have also shown that VHSs constitute a useful intervention for changing behaviour (e.g., Armitage, 2008;Armitage et al, 2016Armitage et al, , 2017Armitage & Arden, 2010Brewster et al, 2015Brewster et al, , 2016Elliott et al, 2021;Paterson et al, 2023). They are also consistent with the findings of Webb et al's (2007) study, which showed that self-generated implementation intentions can increase lecture attendance rates in on-campus lectures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In support of hypothesis 1, university students randomized to a VHS condition attended a significantly greater proportion of synchronous online lectures over the 11-week teaching semester than did students randomly assigned to a control condition (59% vs. 48%). These findings are consistent with previous studies of other behaviours, which have also shown that VHSs constitute a useful intervention for changing behaviour (e.g., Armitage, 2008;Armitage et al, 2016Armitage et al, , 2017Armitage & Arden, 2010Brewster et al, 2015Brewster et al, , 2016Elliott et al, 2021;Paterson et al, 2023). They are also consistent with the findings of Webb et al's (2007) study, which showed that self-generated implementation intentions can increase lecture attendance rates in on-campus lectures.…”
Section: Discussionsupporting
confidence: 92%
“…VHSs have been found to increase smoking cessation (Armitage, 2008), physical activity (e.g., Armitage & Arden, 2010) and weight loss (e.g., Armitage et al, 2017). They have also been found to reduce alcohol consumption (e.g., , driving speed (e.g., Brewster et al, 2015Brewster et al, , 2016, mobile phone use while driving (e.g., Elliott et al, 2021), and self-harm (e.g., Armitage et al, 2016;Paterson et al, 2023). However, no previous studies have tested whether VHSs can increase university students' lecture attendance.…”
Section: Introductionmentioning
confidence: 99%